Providing Memory Management Abstraction for Self-Reconfigurable Video Processing Platforms. (27th July 2009) - Ackermann, Kurt Franz; Hoffmann, Burghard; Indrusiak, Leandro Soares; Glesner, Manfred
Abstract : This paper presents a concept for an SDRAM controller targeting video processing platforms with dynamically reconfigurable processing units (RPUs). A priority-arbitration algorithm provides the required QoS and supports high bit-rate data streaming of multiple clients. Conforming to common video data structures the controller organizes the memory in partitions, frames, lines, and pixels. The raised level of abstraction drastically reduces the complexity of clients' addressing logic. Its uniform interface structure facilitates instantiations in systems with various clients. In addition to SDRAM controllers for regular applications, special demands of reconfigurable platforms have to be satisfied. The aim of this work is to minimize the number of required bus macros leading to relaxed place and route constraints and reducing the number of critical design paths. A suitable interface protocol is presented, and fundamental implementation issues are outlined.